Astrocladistics of the Jovian Trojan Swarms. Issue 2 (1st April 2021) - Holt, Timothy R; Horner, Jonathan; Nesvorný, David; King, Rachel; Popescu, Marcel; Carter, Brad D; Tylor, Christopher C E
ABSTRACT: The Jovian Trojans are two swarms of small objects that share Jupiter's orbit, clustered around the leading and trailing Lagrange points, L4 and L5 . In this work, we investigate the Jovian Trojan population using the technique of astrocladistics, an adaptation of the 'tree of life' approach used in biology. We combine colour data from WISE, SDSS, Gaia DR2, and MOVIS surveys with knowledge of the physical and orbital characteristics of the Trojans, to generate a classification tree composed of clans with distinctive characteristics. We identify 48 clans, indicating groups of objects that possibly share a common origin. Amongst these are several that contain members of the known collisional families, though our work identifies subtleties in that classification that bear future investigation. Our clans are often broken into subclans, and most can be grouped into 10 superclans, reflecting the hierarchical nature of the population. Outcomes from this project include the identification of several high priority objects for additional observations and as well as providing context for the objects to be visited by the forthcoming Lucy mission. Our results demonstrate the ability of astrocladistics to classify multiple large and heterogeneous composite survey data sets into groupings useful for studies of the origins and evolution of our Solar system.